ANALYSIS OF THEME-RHEME AND LOGICAL RELATIONS OF THE SONG LYRICS IN THE ALBUM OF "FOLKLORE" BY TAYLOR SWIFT - Artika Riestiyaningtyas; Mochamad Rizqi Adhi Pratama (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2022)
The study of language refers to discourse analysis. Discourse analysis performs an approach of an analysis connected to the language pattern of a text used in the analysis, it requires linguistic competence. Thematic structure and Grammar are an important role in a sentence. In addition, the Thematic Structure which made up of two parts: Theme and Rheme, The researcher also selects conjunction, which is a component of English grammar. The research was done using the qualitative method. The purpose of this research is to understand and explain about kinds of Themes and Conjunction devices found in the song lyrics of the Album "Folklore" by Taylor Swift. The data was collected through research, reading, collecting, seeing and recording. In this research, the researcher took 10 song lyrics from the Album "Folklore" by Taylor Swift taken by purposive sampling. There are two results of the research, first, the researcher found 745 types of Theme which acquired from 10 song lyrics of the Album "Folklore" by Taylor Swift which were divided into 4 categories. The categories are Topical Theme has 436 occurrences (59%), Interpersonal Theme has 17 occurrences (2%), Textual Theme has 143 occurrences (19%) and Multiple Theme has 149 occurrences (20%). Second, the researcher can conclude that four types of conjunction devices are found in the song lyrics of the Album "Folklore" by Taylor Swift. The using conjunction device found in the song lyrics of the Album "Folklore" by Taylor Swift is 69 (46%) of additive, 28 (19%) adversative, 44 (30%) causal, and 7 (5%) temporal. Based on the results, the researcher found that the most common Theme and conjunctions found in the song lyrics in the Album "Folklore" by Taylor Swift are Topical Themes and Additives Conjunct. Kata Kunci: logical relations, song lyrics, Taylor Swift